Mosque-Based Community Economic Empowerment Strategy: Analysis of Islamic Economic Principles Case Study of Jogokariyan Mosque in Yogyakarta - Sifaudin, Wildan; Djausman, Royyan; Cahyadi, Ady; Abidin, Zaenal (Jurnal Iqtisaduna, 2025)
This research aims to develop a strategy for empowering the masjid-based community economy by analyzing Islamic economic principles. The first thing to know is what the Jogokariyan mosque takmir is implementing, the economic empowerment strategy for the community, and the improvement of the local community's income following the empowerment program. The second objective is to find out the impact of the average income of the surrounding community before and after participating in the masjid jogokariyan community economic empowerment program. To learn the mosque-based economic empowerment strategy of the community, this activity was carried out through interviews with the masjid's manager and questionnaires with the communities who participated in the empowerment program. From the empowerment program, it can be concluded that there was an increase in community income before and after participating in the empowerment program. This activity can foster aalian brotherhood between the takmir of the mosque and the surrounding community so that we can achieve the Khoirul Ummah.